2020
DOI: 10.1007/s00701-020-04477-5
|View full text |Cite
|
Sign up to set email alerts
|

The IDEAL framework in neurosurgery: a bibliometric analysis

Abstract: Background The Idea, Development, Exploration, Assessment and Long-term study (IDEAL) framework was created to provide a structured way for assessing and evaluating novel surgical techniques and devices. Objectives The aim of this paper was to investigate the utilization of the IDEAL framework within neurosurgery, and to identify factors influencing implementation. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The Exploration Stage outlines the process of reaching a collective understanding of the procedure between operators from different centres, to address obstacles to a definitive comparative trial, including reaching agreement about standard technique and accepted variants. This study highlights this crucial step that should be a requirement in the development of neurosurgical innovation [ 26 , 27 ]. Accordingly, the NEL protocol produced through this consensus study will serve as a valuable tool in the design of a collaborative randomised clinical trial to determine the efficacy of NEL, in line with stage 3 of the IDEAL Framework.…”
Section: Discussionmentioning
confidence: 99%
“…The Exploration Stage outlines the process of reaching a collective understanding of the procedure between operators from different centres, to address obstacles to a definitive comparative trial, including reaching agreement about standard technique and accepted variants. This study highlights this crucial step that should be a requirement in the development of neurosurgical innovation [ 26 , 27 ]. Accordingly, the NEL protocol produced through this consensus study will serve as a valuable tool in the design of a collaborative randomised clinical trial to determine the efficacy of NEL, in line with stage 3 of the IDEAL Framework.…”
Section: Discussionmentioning
confidence: 99%
“…The Exploration Stage outlines the process of reaching a collective understanding of the procedure between operators from different centres, to address obstacles to a definitive comparative trial, including reaching agreement about standard technique and accepted variants. This study highlights this crucial step that should be a requirement in the development of neurosurgical innovation [25, 26]. Accordingly, the NEL protocol produced through this consensus study will serve as valuable tool in the design of a collaborative randomised clinical trial to determine the efficacy of NEL, in line with Stage 3 of the IDEAL Framework.…”
Section: Discussionmentioning
confidence: 96%
“…However, there is some data to suggest that the IDEAL and similar frameworks are being adopted, albeit slowly, within the neurosurgical community. In a recent bibliometric analysis Ota et al found 51 studies that cited IDEAL with the overwhelming majority being positive [ 77 ].…”
Section: Discussionmentioning
confidence: 99%